Pola Mata Pencaharian Tradisional Dalam Masyarakat Kajang Studi Etnografi Tentang Kesejahteraan Ekonomi - Haniifah Nabilah; Tan, Garvin Christoper; Jusni (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This study was conducted to analyze and identify how the traditional livelihood patterns are carried out by the Kajang community, as one of the communities that still maintains the form of local wisdom that it has, so research becomes a form of study to provide an overview of the traditional livelihood patterns of the community and how they are able to utilize natural resources as basic livelihood materials or in meeting daily needs. The writing of this article is intended to find out how the livelihood patterns of the Kajang tribe are in identifying the level of welfare owned by each individual in the community, and also the urgency regarding the role of each community not only in the economic field but also social, cultural, and also government in the Kajang community with a fairly complex pattern. This study uses a qualitative approach based on ethnography to explain and analyze individual or group phenomena, events, social dynamics, attitudes, beliefs, and perceptions. So that through the process of identification and analysis, it can produce structured and relevant research in accordance with the data collected regarding the level of welfare of the Kajang tribe through their livelihood patterns.